Perinsip Kehati-Hatian Dalam Proses Penerbitan Sertifikat Hak Atas Tanah Oleh Kantor Badan Pertanahan Nasional (BPN) Di Kabupaten Lombok Timur - Karya Pramana, Panji (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2024)
This research is a type of normative, empirical legal research which is prescriptive in nature. This research data uses legal materials. Legal materials were collected using library study techniques. The analysis technique used is syllogism deduction with the method of language interpretation (grammatical) and systematic interpretation, with legal rules regarding land seen as the major premise, and the minor premise in the form of juridical facts, namely the State Administrative Court's decision regarding a lawsuit against the above certificate of ownership. the same plot with Building Use Rights. From the results of the research and discussion, it was concluded that the East Lombok Regency Land Office was less careful in issuing certificates over ownership rights, as an arbitrary act that was detrimental to other parties, because certificates had already been issued over the ownership rights. Building Use Rights for the same plot and the evidentiary strength of the certificate have the power as strong evidence if within a period of 5 years from issuance there are no objections or claims from other parties